The economic impact of the Covid-19 pandemic on the United Kingdom. - rakha, ahmed (2020)
The COVID-19 pandemic has brought economic activity to a near standstill as many countries imposed very strict restrictions on movement to halt the spread of the virus. This can be observed by the widespread lockdowns, social distancing measures placed globally and significant disturbances in the local supply chains. Although the damaging effect of this crisis is expected, the magnitude of the impacts remains to be defined. Real economic performance data needs to be collected and analysed to be able to form conclusions and make an accurate prediction of the economic impact of the Covid-19 pandemic. This study aimed to assess the economic effects of COVID-19 pandemic in the United Kingdom (UK) using available data up to 7 months following the start of the crisis. The macroeconomic indicators, Gross Domestic Products (GDP) and GDP growth, and the firm performance indicators (Return on Asset and Tobin’s q) were assessed. The impacts were evaluated on the three primary industries in the UK; Construction, Production and Service to determine any potential variations and allow comparison with the previous outbreaks related data. This study found that the UK economy was significantly affected by the pandemic resulting in the largest drop in GDP that the UK has ever encountered (-20.4) with more than seven times drop compared to any previous economic shocks. The impact was also different in the different industries; the construction industry suffered 1.7 times more than the service industry (-35.0 and -19.9, respectively). However, the magnitude of impact on each sector was different from previous outbreaks. This study provided evidence-based data on the economic effects of COVID-19 that can be used to guide the UK government in the prediction of future impacts and to take appropriate actions to support the economy.